Vorausberechnung von Verwandtschaft Wie sich die gemeinsame Lebenszeit von Kindern, Eltern und Großeltern zukünftig entwickelt - Dudel, Christian (Beitrage zur Bevölkerungswissenschaft, 2014)
Close relatives such as parents and children play an important role in the daily lives of many people. In view of demographic change - increasing life expectancy and declining birth rates - the question arises as to how the presence of relatives will change in the future. This question is explored in the present book and the possible effects of future changes on the common lifetime of generations and on the field of care are examined.